The role of senolytics in osteoporosis and other skeletal pathologies. (October 2021) - Doolittle, Madison L.; Monroe, David G.; Farr, Joshua N.; Khosla, Sundeep
Graphical abstract: Alleviation of cellular senescence in the bone microenvironment with senolytic therapy. Aging, onco-therapies (radiation and chemotherapy), and Type 2 Diabetes Mellitis (T2DM) lead to increased inflammation in the bone microenvironment through the senescent-associated secretory phenotype (SASP) exhibited by senescent osteoprogenitors, osteocytes, and myeloid cells, among others. This state is associated with reduced bone formation and increased bone resorption, leading to reduced bone mass. Senolytic treatment targets and clears senescent cells, which alleviates SASP-mediated inflammation and allows for repopulation of non-senescent osteoblasts on the bone surface, leading to enhanced bone formation, reduced resorption, and improved bone mass. Highlights: Senescent cells accumulate in bone with aging and systemic pathologies. Clearance of senescent cells alleviates bone loss in old mice. Novel senolytics are being discovered and tested in bone. Abstract: The skeletal system undergoes irreversible structural deterioration with aging, leading to increased fracture risk and detrimental changes in mobility, posture, and gait. This state of low bone mass and microarchitectural changes, diagnosed as osteoporosis, affects millions of individuals worldwide and has high clinical and economic burdens. Recently, pre-clinical studies have linked the onset of age-related bone loss with an accumulation of senescent cells in the bone microenvironment. These senescent cells appear to be causal to age-related bone loss, as targeted clearance of these cells leads to improved bone mass and microarchitecture in old mice. Additionally, other pathologies leading to bone loss that result from DNA damage, such as cancer treatments, have shown improvements after clearance of senescent cells. The development of new therapies that clear senescent cells, termed "senolytics", is currently underway and may allow for the modulation of bone loss that results from states of high senescent cell burden, such as aging.